2022
DOI: 10.4103/tcmj.tcmj_20_22
|View full text |Cite
|
Sign up to set email alerts
|

The impact of holiday season and weekend effect on traumatic injury mortality: Evidence from a 10-year analysis

Abstract: A BSTRACT Objectives: Trauma is one of the leading causes of death and its incidence increases annually. The “weekend effect” and “holiday season effect” on traumatic injury mortality remain controversial, whereby traumatic injury patients admitted during weekends and/or holiday season have a higher risk of in-hospital death. The present study is aimed to explore the association between “weekend effect” and “holiday season effect” and mortality in traumatic injury popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Traumatic injury is a major global health problem, contributing to both mortality and disability and placing a substantial burden on healthcare systems [1]. Several triage tools have been developed for use in both prehospital and hospital settings, including the Canadian Triage and Acuity Scale (CTAS) [2], the Emergency Severity Index (ESI) [3], the Manchester Triage Scale [4], the Taiwan Triage and Acuity Scale (TTAS) [5,6], and the Australasian Triage Scale [7].…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic injury is a major global health problem, contributing to both mortality and disability and placing a substantial burden on healthcare systems [1]. Several triage tools have been developed for use in both prehospital and hospital settings, including the Canadian Triage and Acuity Scale (CTAS) [2], the Emergency Severity Index (ESI) [3], the Manchester Triage Scale [4], the Taiwan Triage and Acuity Scale (TTAS) [5,6], and the Australasian Triage Scale [7].…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, level 1 trauma centers, which are accredited on the basis of their emergency capacity, have attending surgeons available 24/7 for all major trauma resuscitations. These centers also provide resuscitation interventions such as transcatheter arterial embolization or surgery, even on weekends and holidays [ 6 , 8 ]. Although studies have reported the optimal time to definitive care to be 2 h for procedures such as exploratory laparotomy and craniotomy at level 1 hospitals, in Taiwan, the time limit for emergent trauma surgeries is typically 30 min [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%